Treatment perspectives and challenges in antifungal therapy for mucormycosis in patients with COVID-19 (Research, Society and Development, 2025)
The COVID-19 pandemic has led to an increase in opportunistic infections, such as mucormycosis, better known as “black fungus”, which has become prevalent in various parts of the world, especially in India. This fungal infection is highly debilitating and has high rates of morbidity and mortality, with antifungal therapy focused on conventional antifungal drugs with or without successful treatment. Therefore, the objective of this study was to identify the main perspectives and challenges caused by antifungal treatment in patients who acquired COVID-19 and, consequently, mycosis caused by fungi of the order Mucorales. To this end, an integrative literature review was carried out based on a five-step planning: elaboration of the research question (identification of the problem), search for studies in the literature, evaluation of the studies, data analysis, and presentation of the review, which used the PICO strategy. During the search in the databases, 292 studies were initially found (Science Direct=112, PubMed=35, Scielo=1 and MEDLINE=144), of which 38 studies were included. Among the studies, it was noted that there is a greater need for early diagnosis, as well as the production of intensive clinical management, especially for patients with comorbidities; and there is also a lack of production of specific protocols for cases of mucormycosis related to COVID-19 in order to improve clinical outcomes.